John G. Diefenbaker remarks - Diefenbaker, John G., 1895-1979.
Remarks relating to the exchange of documents between Canada and the United States
Prime minister of Canada.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Canada -- Relations -- United States; United States -- Relations -- Canada; Prime ministers -- Canada